Transforming Entrepreneurship Education Interdisciplinary Insights on Innovative Methods and Formats - Halberstadt, Jantje; Alcorta de Bronstein, Antonieta; Greyling, Jean.; Bissett, Shaun; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2023)
This open access book provides selected teaching approaches, supporting methods, concrete examples of curricula as well as extracurricular teaching formats, which are predominantly tailored to both African and German requirements. These approaches were developed by the YEEES Training and Research Centers, an international interdisciplinary network of university teachers and researchers from Germany and southern Africa, and combine the fields of management, entrepreneurship, information and communication technologies (ICT), and sustainability. The book shows how current scientific results can be integrated into teaching, how students can contribute to research while learning, and how research can contribute to the development and evaluation of new formats. It is thus relevant for university teachers, researchers, students as well as practitioners who want to educate and act as future change agents.
Part 1. Teaching Approaches and Support -- Chapter 1. Teaching Transformative Service Learning -- Chapter 2. Challenge-based Learning: How to Support the Development of an Entrepreneurial Mindset -- Chapter 3. Developing Responsible and Sustainable Innovations in Entrepreneurship Education - Introducing the Sandbox Approach -- Chapter 4. Using Moodle to Teach Computer Literacy to First Time Computer Users: A Unam Case Study -- Part 2. Formats -- Chapter 5. Transformational Sustainability Entrepreneurship: Encouraging Students to Become Change Agents -- Chapter 6. Insights Into an Action-oriented Training Program to Promote Sustainable Entrepreneurship -- Chapter 7. Introducing an Innovative International Format for Experience-based Sustainability Entrepreneurship Education: The YEEES Sustainability Camps -- Chapter 8. Transdisciplinary Learning Experiences in an Urban Living Lab: Practical Seminars as Collaboration Format -- Chapter 9. Using Unplugged Tools to Introduce Coding to South African Learners -- Part 3. Research -- Chapter 10. I Would Help the Lecturer with Marking: Entrepreneurial Education Insights on Academic Resilience from the Perspectives of Engineering Students in South Africa -- Chapter 11. Measuring the Success of Innovative Entrepreneurship Education in Universities: Impact Clusters and the Importance of Entrepreneurial Intention.
Keywords: Entrepreneurship; New business enterprises; Education; Sustainability; Education -- Data processing; Teachers -- Training of; Entrepreneurship; Education; Sustainability; Computers and Education; Teaching and Teacher Education